2019
DOI: 10.1145/3305218.3305223
|View full text |Cite
|
Sign up to set email alerts
|

SRPT for Multiserver Systems

Abstract: The Shortest Remaining Processing Time (SRPT) scheduling policy and variants thereof have been deployed in many computer systems, including web servers [5], networks [9], databases [3] and operating systems [1]. SRPT has also long been a topic of fascination for queueing theorists due to its optimality properties. In 1966, the mean response time for SRPT was first derived [11], and in 1968 SRPT was shown to minimize mean response time in both a stochastic sense and a worst-case sense [10]. However, these beaut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…To our knowledge, the first analytic results on the M/G/k/SRPT were given by Grosof et al (2018). They proved analytic bounds on the mean response time of the M/G/k/SRPT.…”
mentioning
confidence: 87%
“…To our knowledge, the first analytic results on the M/G/k/SRPT were given by Grosof et al (2018). They proved analytic bounds on the mean response time of the M/G/k/SRPT.…”
mentioning
confidence: 87%
“…Given the optimality of the Shortest-Remaining-Processing-Time (SRPT) policy in the degenerate case where k = 1 [48], one might hope that SRPT is also optimal in the multiserver case where k ≥ 2. Specifically, one might consider a policy called SRPT-k [19] which always runs the k jobs with the shortest remaining processing times. Unfortunately, [35] shows that SRPT-k can be arbitrarily far from optimal.…”
Section: Why Stochastic Analysis?mentioning
confidence: 99%
“…Much of the prior work has been limited to scheduling jobs on a single server [11]. While there has certainly been work on scheduling in stochastic multiserver systems (e.g [1,6,19,23,24,29]), this literature assumes that a job occupies at most one server at a time (that is, all jobs are inelastic). One notable model that considers jobs that run on multiple servers is the queueing model motivated from MapReduce [32,42,50].…”
Section: Prior Workmentioning
confidence: 99%
“…Gieroba and Kruk [25] investigated some pathwise minimality properties associated with the SRPT protocol in resource sharing networks. Grosof et al [27] provided bounds for the mean response time in the M/G/k queue under the SRPT and showed asymptotic optimality of this mean response time in the heavy-traffic limit. Recently, Dong and Ibrahim [22] investigated the multiserver M/G/k+G queue with impatient customers under the SRPT protocol and showed that, in the many-sever overloaded regime, its performance is asymptotically equivalent in steady state to a preemptive two-class priority queue.…”
Section: Introductionmentioning
confidence: 99%